Review: Peran Protein Virus dalam Host Immune System Evasion - Nurhaifa Azzahra; Nazif Muhammad; Wulan Pertiwi (Jurnal Biodiversitas dan Bioteknologi, 2025)
The human body has an immune system that functions to protect the body from pathogens such as bacteria and viruses. This system consists of two types of immunity: non-specific immunity (innate immunity) and specific immunity (adaptive immunity). Non-specific immunity acts quickly using various cells and molecules to combat pathogens, while specific immunity takes longer but is more effective and has the ability to remember pathogens for a faster response in the future. Despite this, many viruses have developed mechanisms to evade detection and elimination by the immune system, known as immune evasion. This evasion is carried out in various ways, including modifications of viral proteins that disrupt immune pathways, such as antigen presentation, interferon signaling, and immune cell functions. This literature review aims to identify the various strategies used by viruses to evade the immune system. The method used is a literature search from various scientific journals such as PubMed, Wiley, and Elsevier. The analysis results show that viruses can avoid PRR detection, inhibit JAK-STAT signaling, and regulate autophagy to survive and replicate within the host body. This study provides an in-depth understanding of the immune evasion mechanisms by viruses, which are a major challenge in the treatment and prevention of infectious diseases. A deep understanding of these immune evasion mechanisms in crucial for developing more effective strategies to fight viral immune evasion, thereby enhancing the effectiveness of therapies and vaccines in the treatment and prevention of infectious diseases